Bipyridine-phenolate based aluminum complexes mediated ring-opening polymerization of ε-caprolactone and lactides with a high stereoselectivity. (18th August 2015) - Hsieh, Yi-Liang; Huang, Ning; Lee, Gene-Hsiang; Peng, Chi-How
Abstract: Aluminum complexes coordinated by bipyridine-phenolate (BpyPh ) ligands of 2-([2, 2′-bipyridin]-6-yl)-4, 6-di-tert-butylphenol (BpyPh 2, 4-tBu -H), 2-([2, 2′-bipyridin]-6-yl)-4-(tert-butyl)phenol (BpyPh 4-tBu -H), and 2-([2, 2′-bipyridin]-6-yl)-4, 6-dimethylphenol (BpyPh 2, 4-Me -H) have been synthesized and applied to mediate the ring-opening polymerization (ROP) of ε-caprolactone (ε-CL) andl -lactide (L-LA) in the presence of benzyl alcohol. The living characters of predictable molecular weight, narrow molecular weight distribution, and the formation of block copolymer were observed in the polymerization mediated by (BpyPh 2, 4-tBu )AlMe2 and all three complexes associated with benzyl alcohol could initiate the ROP of ε-CL and L-LA. The iso-selectivity of rac -lactide polymerization could be enhanced from P m  = 0.38 to P m  = 0.75 by increasing the steric hindrance of ortho -substituent on phenol group of the ligand. Graphical abstract: Highlights: Designed ligands were obtained via a simple, one pot reaction. Well controlled ring-opening polymerization of various cyclic esters was achieved. The iso-selectivity of rac -lactide polymerization could be enhanced to P m  = 0.75.